Fluorescence imaging of hepatocellular carcinoma with a specific probe of COX-2. Issue 2 (3rd January 2018) - Wang, Haibo; Dong, Chengyong; Jiang, Keqiu; Zhang, Shuangzhe; Long, Fei; Zhang, Rixin; Sun, Deguang; Liang, Rui; Gao, Zhenming; Shao, Shujuan; Wang, Liming
Abstract : Hepatocellular carcinoma (HCC) is the major subtype of primary liver cancer. Abstract : Hepatocellular carcinoma (HCC) is the major subtype of primary liver cancer. Although the standard treatment method based on surgery has generally extended life, it still causes the second and sixth most prevalent cancer-related death in men and women, respectively. The recurrence of cancer caused by unclear resection margins and any remaining undiscovered metastatic nodules should take a large proportion of responsibility for the poor prognosis after resective surgery. Therefore, a practical and effective method that can be used during hepatectomy to specifically identify HCC is a potentially significant area deserving attention. Tests involving fluorescence have been used in many biological systems. In this study, we use a probe that can combine with cyclooxygenase-2 (COX-2) and subsequently emit fluorescence to identify HCC cells and heteroplastic tumors in a mouse model. The results show that this specific probe can clearly differentiate HCC, with differences that could be observed with the naked eye in human samples. The biotechnology of knocking down COX-2 and its inhibitor were used on human HCC cell line SMMC7721, and the outcomes confirmed the above results. The toxic effect also showed that the probe had no harmful effect on normal liver cells. Taken together, our study demonstrates that a COX-2-specific fluorescence probe may be a new and effective method to identify HCC, especially during surgery.